Influence of modification of RZM on crack resistance of the cast boron-containing material - N. F. Nevar; Ju. N. Fasevich (Литьë и металлургия, 2003)
There is shown, how modification of the rare-earth metals influences on crack-resistance of the cast boron-containing material.